2008
DOI: 10.1021/ja802177u
|View full text |Cite
|
Sign up to set email alerts
|

Interstrand Cross-Link Formation in Duplex and Triplex DNA by Modified Pyrimidines

Abstract: DNA interstrand cross-links have important biological consequences and are useful biotechnology tools. Phenylselenyl substituted derivatives of thymidine (1) and 5-methyl-2′-deoxycytidine (5) produce interstrand cross-links in duplex DNA when oxidized by NaIO 4 . The mechanism involves a [2,3]-sigmatropic rearrangement of the respective selenoxides to the corresponding methide type intermediates, which ultimately produce the interstrand cross-links. Determination of the rate constants for the selenoxide rearra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 28 publications
1
63
0
2
Order By: Relevance
“…10,11 However such ICLs are highly dependent on the proper positioning of thiol groups and, more importantly, require modification of both strands. More recent studies on site-specific ICL formation involve modified phenylselenyl derivatives of thymidine or 5-methyl-2 0 -deoxycytidine, 12 1,4-dioxobutane abasic lesion, 13 alkyl-connected 2-amino-6-vinylpurine 14 and 4-amino-6-oxo-2-vinylpyrimidine. 15 We have earlier developed a complementary methodology incorporating furan-modified 2 0 -amido-uridine and an acyclic building block to give a site-specific ICL upon oxidation with Nbromosuccinimide (NBS).…”
mentioning
confidence: 99%
“…10,11 However such ICLs are highly dependent on the proper positioning of thiol groups and, more importantly, require modification of both strands. More recent studies on site-specific ICL formation involve modified phenylselenyl derivatives of thymidine or 5-methyl-2 0 -deoxycytidine, 12 1,4-dioxobutane abasic lesion, 13 alkyl-connected 2-amino-6-vinylpurine 14 and 4-amino-6-oxo-2-vinylpyrimidine. 15 We have earlier developed a complementary methodology incorporating furan-modified 2 0 -amido-uridine and an acyclic building block to give a site-specific ICL upon oxidation with Nbromosuccinimide (NBS).…”
mentioning
confidence: 99%
“…PhSe-T has been shown to produce an ICL with the opposing dA upon UV photolysis through a 5-(2 0 -deoxyuridinyl) methyl radical intermediate or upon oxidation through a methide intermediate [10][11][12][13][14]. MeSe-T, which was recently synthesized using a similar synthetic method to that of PhSe-T, triggered similar apoptotic signaling pathways as PhSe-T and showed more toxicity than PhSe-T in all cell lines used in this study [15].…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown that phenylselenide derivative 5-phenylselenyl-methyl-2 0 -deoxyuridine (PhSe-T) can be incorporated into DNA by DNA polymerases and can produce ICLs with the opposing strand 2 0 -deoxyadenosine (dA) [10][11][12][13][14]. The nucleoside derivative 5-methylselenylmethyl-25-phenylselenyl-methyl-2 0 -deoxyuridine-deoxyuridine (MeSe-T) was recently synthesized following a similar synthetic method as PhSe-T, and its molecular structure is identical to that of PhSe-T, except for replacement of the phenyl group with a methyl group [15] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structures of several DNA interstrand crosslinks have been reported only recently. Several groups have focused on the identification of ICL structures synthesized in model systems using light-and/or oxidationsensitive precursors (Hong et al, 2006;Weng et al, 2007;Peng et al, 2008;Kim & Hong, 2008;Op de Beeck & Madder, 2011). A few structures have been definitively identified in natural conditions and, to our knowledge, only one in cellular DNA (Regulus et al, 2007) (Fig.…”
Section: Mechanistic and Structural Aspects Of The Icl Formation In Dmentioning
confidence: 99%